Oral health education and methods for detecting the replacement of deciduous teeth with permanent teeth - Roro Ambar Arini; Rahmania Ade Fitriani; Naufal Hanif Syah Novildan; Edwyn Saleh; Aji Nugroho; Sri Utami; Sartika Puspita (Universitas Muhammadiyah Magelang, 2024)
Indonesian people's awareness of oral health is still relatively low, as evidenced by the number of people who seek dental treatment and check-ups only when experiencing dental problems. Based on this issue, promotive and preventive efforts are needed through oral health education. The oral health status of the people in Dusun Botokan shows that many people do not have their teeth and mouths checked. Therefore, the purpose of this community service activity is to improve the knowledge and healthy behaviors of the people of Dusun Botokan regarding oral health. The method used is education as a promotive and preventive effort, as well as medical services as a curative effort. The success of the activity is seen from the short-term results in the form of an increase in pre-test and post-test scores by 12.74%. Thus, this activity has succeeded in increasing the knowledge of tooth replacement detection and awareness of oral care in the community of Dusun Botokan.